The Achilles Heel of Rehabilitation: Communication: A First Look at a National Research Survey. Issue 4 (16th October 2019) - Jenkins, David; Urness, Daniel; Thompson, Austin; Meeker, James
Category: Hindfoot, Rehabilitation Introduction/Purpose: For decades, there has been much debate over the proper treatment and rehabilitation protocols regarding the management of Achilles tendon ruptures (ATRs). With so much controversy, communication between physical therapists (PTs) and orthopaedic surgeons could prove to be paramount in ensuring successful recovery and return to post- morbid activities. Little research has been done in identifying effective communication modalities between surgeons and PTs and it remains unclear how this dynamic impacts the rehabilitation course. We examined the frequency of how common it is for PTs to receive rehabilitation protocols from referring orthopedic surgeons in patients who suffered Achilles tendon ruptures. Methods: A blinded national research survey was conducted of PTs who had treated ATR from 2012-2017. Researchers sought to create a generalizable sample of US PTs by selecting physical therapy clinics located in rural and urban areas of randomly selected states. Those who were actively practicing as a PTs and held a corresponding degree (DPT, MPT, and MSPT) were included. Non-practicing PTs, and those without a degree in physical therapy were excluded. A total of 56 respondents took part in the survey. Results: PTs practicing for 10 or more years were more likely to promote slower rehabilitation for non-surgical patients, while PTs with less than 10 years of experience preferred slower progress for operative patients (p=0.04). PTs with 10 or more years of experience were significantly more likely to have patients full weight bearing (FWB) after 6 weeks (p=0.01). PTs were also asked what factor was most important for good ATR outcomes. Three themes emerged, one was good communication between PTs and doctors. One respondent wrote "better communication between MD and PT for best outcomes." The second theme was timing and implementation of proper clinical techniques such as "early ROM and weight bearing." A final theme centered on patient education, especially physicians educating patients on mobility restrictions. Conclusion: Despite belief that protocol driven approach improves outcomes, it remains unclear how well applied this is in practice. One of the most common responses given by PTs when asked what the most important factor is to ensure good outcomes in ATRs was good communication between PTs and doctors. This insight juxtaposed with 49% of PTs stating most of their recent patients arrived with no protocol, suggests one way to help improve patient outcomes might be to focus on improving communication between doctors and PTs.